Sortase A-Cleavable CD1d Identifies Sphingomyelins as Major Class of CD1d-Associated Lipids - Rudolph, Maren; Wang, Yuting; Simolka, Theresa; Huc-Claustre, Emilie; Dai, Lingyun; Grotenbreg, Gijsbert; Besra, Gurdyal Singh; Shevchenko, Anna; Shevchenko, Andrej; Zeissig, Sebastian (Frontiers in Immunology, 2022)
CD1d is an atypical MHC class I molecule which binds endogenous and exogenous lipids and can activate natural killer T (NKT) cells through the presentation of lipid antigens. CD1d surveys different cellular compartments including the secretory and the endolysosomal pathway and broadly binds lipids through its two hydrophobic pockets. Purification of the transmembrane protein CD1d for the analysis of bound lipids is technically challenging as the use of detergents releases CD1d-bound lipids. To address these challenges, we have developed a novel approach based on Sortase A-dependent enzymatic release of CD1d at the cell surface of live mammalian cells, which allows for single step release and affinity tagging of CD1d for shotgun lipidomics. Using this system, we demonstrate that CD1d carrying the Sortase A recognition motif shows unimpaired subcellular trafficking through the secretory and endolysosomal pathway and is able to load lipids in these compartments and present them to NKT cells. Comprehensive shotgun lipidomics demonstrated that the spectrum and abundance of CD1d-associated lipids is not representative of the total cellular lipidome but rather characterized by preferential binding to long chain sphingolipids and glycerophospholipids. As such, sphingomyelin species recently identified as critical negative regulators of NKT cell activation, represented the vast majority of endogenous CD1d-associated lipids. Moreover, we observed that inhibition of endolysosomal trafficking of CD1d surprisingly did not affect the spectrum of CD1d-bound lipids, suggesting that the majority of endogenous CD1d-associated lipids load onto CD1d in the secretory rather than the endolysosomal pathway. In conclusion, we present a novel system for the analysis of CD1d-bound lipids in mammalian cells and provide new insight into the spectrum of CD1d-associated lipids, with important functional implications for NKT cell activation.